Investigating the Effect of Thermal Conductivity of Salt Water and Bottom Reflectivity on the Performance of the Salt Gradient Solar Pond - Sunil Kumar; S. K. Singh (New Approaches in Engineering Research Vol. 13, 2021)
The presence of undissolved salt and the deposition of dirt at the bottom of the prototype salt gradient solar pond leads in an increase in reflectivity. The efficiency of the solar pond decreases linearly with the reflectivity of the bottom of the pond. Salt concentration and temperature affect the thermal conductivity of salt water. The temperature of the pond surface is assumed to be the same as that of the surrounding air. This research investigates the impact of various parameters on the efficiency of solar pond collectors. The impact of dirt and reflections at the pond’s bottom have also been considered.